2019
DOI: 10.1021/acssuschemeng.9b01286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brine Water on Discharge of Cations in Membrane Capacitive Deionization and Its Implications on Nitrogen Recovery from Wastewater

Abstract: The ion desorption behavior from carbon electrodes onto high concentration brine was examined in this work because the ionic resources in brine are accumulated to attain high concentration in membrane capacitive deionization (MCDI) during mineral resource recovery. Several major issues were explored to demonstrate the suitability of MCDI for mineral recovery: ion discharge behavior using different solution chemistries (0 to 10 mM of NaCl, KCl, and MgCl2) of feed and brine, desorption efficiencies of various el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…By putting the environmentally friendly factors into life cycle assessment consideration, on average MCDI system had 5,641 fewer values for damage assessment categories than RO system. Kim et al (2019a) tested the behavior of cations desorption from the cathode into the brine stream using solutions with different chemical compositions; efficiency of the desorption using different regeneration methods; cations desorption selectivity. With the ionic-strength gradient increases in the brine, the cation desorption efficiency was retarded during the recovery.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…By putting the environmentally friendly factors into life cycle assessment consideration, on average MCDI system had 5,641 fewer values for damage assessment categories than RO system. Kim et al (2019a) tested the behavior of cations desorption from the cathode into the brine stream using solutions with different chemical compositions; efficiency of the desorption using different regeneration methods; cations desorption selectivity. With the ionic-strength gradient increases in the brine, the cation desorption efficiency was retarded during the recovery.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
“…Kim et al (2019) and Kim, Nakhla, and Keleman (2019) studied the binding and transport of cations in membrane capacitive deionization (MCDI) using a cation exchange membrane (CEM) to recover minerals and found that the order of release of cations was potassium, followed by sodium and magnesium. They reported that the diffusion rate of the cations and their valence were the primary factors governing their release.…”
Section: Membrane Treatment Technologiesmentioning
confidence: 99%
“…BioWin software was used to predict the impact of food waste on nutrient removal, biogas generation, and energy balance for 114 scenarios using various technologies (Kim et al, 2019; Kim et al, 2019). Addition of food waste produced effluents with lower effluent nitrogen (3.6–7.9.g/L for BNR; 0.6–1.3 mg/L for A2O; 1.0–2.3 mg/L for Bardenpho), reduced operating costs of between 25% and 78% for various processes analyzed, and produced a net energy gain of 3,300–3,700 kWh/day for a 10 MGD plant.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The domestic wastewater depth processing for secondary effluent is required to meet effluent quality standards and reuse wastewater resources. 4,5 The efficiency of a secondary effluent treatment depends on the performance of biological aerated filters (BAFs) that are most commonly employed for secondary effluent treatment. 6 BAF was developed in Europe in the late 1980s using the principle of filter media.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 Various cost-effective materials have been utilized to bridge this gap. However, the existing literature on BAF is primarily focused on the removal of either nitrogen alone 4,8 or both phosphate and nitrogen. 9 Nonetheless, to the best of the authors' knowledge, limited work is focused on the simultaneous phosphate recovery and nitrogen removal (SPN) in BAF, which is an urgent requirement for resource recovery from wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%